Simulasi dan Analisis Tegangan Sensor LDR dengan OP-AMP Berbeda - Dewi Lestari; Ramadhan Dwi Purnomo (Universitas Islam Negeri Alauddin Makassar, 2023)
The development of the accelerated pace of technology makes people motivated to make new innovations, as well as something that can be controlled automatically. Therefore, we need a sensor that can facilitate human activities, especially in the home light control system. The purpose of this study is to test and analyze the LDR sensor by simulating a software, namely Proteus with different op-amps. LDR (Light Dependent Resistor) is a type of resistor whose resistance value depends on the intensity of light. The method used in this research is an experimental method, namely by conducting repeated tests 10 times for different types of op-amps. The tests carried out here use three ICs that have different types, namely IC LM 358, IC LM741 and IC LM747. The results of this study are the average voltage value generated for the IC LM385 input 2.75 Volt and 4.99 Volt, IC LM 741 input 2.74 Volt and 2.62 Volt and IC OP07 2.77 Volt input and output 2.5 Volts. Of the three IC test results, the largest average voltage value for both input and output is the OP-AMP LM385 IC.